VSL#3 Probiotic Upregulates Intestinal Mucosal Alkaline Sphingomyelinase and Reduces Inflammation - Isaac Soo; Karen L Madsen; Qassim Tejpar; Beate C Sydora; Richard Sherbaniuk; Benedetta Cinque; Luisa Di Marzio; Maria Grazia Cifone; Claudio Desimone; Richard N Fedorak (Canadian Journal of Gastroenterology)
BACKGROUND: Alkaline sphingomyelinase, an enzyme found exclusively in bile and the intestinal brush border, hydrolyzes sphingomyelin into ceramide, sphingosine and sphingosine-1-phosphate, thereby inducing epithelial apoptosis. Reduced levels of alkaline sphingomyelinase have been found in premalignant and malignant intestinal epithelia and in ulcerative colitis tissue. Probiotic bacteria can be a source of sphingomyelinase.